Seroprevalence of hepatitis C in haemodialysis patients in tertiary care hospital in Punjab - Kaur, Jaspal; Oberoi, Loveena; Singh, Kanwardeep; Chander, Rakesh (International Journal of Research in Medical Sciences, 2022)
Background: Hepatitis C is an emerging infectious disease all over the world especially in the developing countries. HCV is a blood borne virus, well known risk factors include blood transfusion, injection drug abuse, chronic haemodialysis patients. HCV is a single stranded positive sense RNA virus, belongs to family flaviviridae and genus Hepacivirus. Haemodialysis patients are the high risk group due to prolonged vascular access and contaminated equipments. Methods: The present study was retrospective conducted from June 2019 to 31 July 2020 in the Department of Microbiology, Government Medical College, Amritsar. Clinical, demographic and geographical data of the renal disease patients admitted to the hospital for haemodialysis was recorded and analysed. The patients were tested for HCV by Third Generation ELISA. Results: In the present study, out of enrolled 186 patients, 12 were HCV positive (0.06%). Prevalence of Hepatitis C infection in haemodialysis patients is associated with gender distribution more in females (72%) than males (62%), preponderance of HCV infection was observed in age group 41-60 years (69%) followed by 21-40 years (23%),more rural (85%) distribution. Diabetes (19%), hypertension (25%) and chronic kidney disease (63%) were the associated comorbid conditions. Conclusions: The overall HCV sero prevalence was observed to be 0.06%, this low prevalence can be attributed to the fact that increased awareness regarding the disinfection of dialysis machines by improving the surveillance system of HCV and better education of nurses in dialysis units. HD patients should be routinely screened for HCV infection.